Meningkatkan Kemampuan Berbahasa Anak Usia Dini Melalui Metode Bercerita - Sovia Ikhwani Putri (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
This research aims to explore and analyze the effectiveness of storytelling methods in enhancing the language skills of early childhood. This method was chosen as the main focus due to its potential to stimulate language development during the critical period of child growth. The study employed an experimental approach, involving two groups—control and intervention—comprising children aged 3-5 years from a local kindergarten. The intervention group participated in structured storytelling sessions designed to stimulate language comprehension, vocabulary, and speaking skills. Meanwhile, the control group engaged in conventional learning activities without a specific focus on storytelling methods. Data were collected through observation, written tests, and interviews with teachers and parents. The research results demonstrate a significant improvement in language abilities within the intervention group compared to the control group. Children involved in the storytelling method showed substantial enhancements in language comprehension, verbal expression, and vocabulary mastery. These findings support the hypothesis that storytelling methods can be effective as a learning approach to enhance the language abilities of early childhood.